PLUTO'S SATELLITE HYDRA - Vidmachenko , Anatoliy (Collection of scientific papers «ΛΌГOΣ», 2025)
The "New Horizons" team suspected that Pluto and Charon might have other small moons and rings around them. Remote sensing data from the Hubble Space Telescope were used to test this hypothesis. In May 2005, this led to the discovery of the Nix and Hydra satellites. It is believed that all of Pluto's smaller moons were formed from debris ejected from a powerful collision between Pluto and another Kuiper Belt object. The debris from this collision eventually coalesced into Pluto and all of its moons. Due to tidal interactions, Hydra's orbit around the Pluto-Charon barycenter gradually became more circular over time. Images from the "New Horizons" spacecraft in July 2015 with detailed images of the satellite Hydra, for the first time allowed us to determine the dimensions of this satellite quite accurately: 50.9 km × 36.1 km × 30.9 km. Hydra turned out to be the second largest satellite of Pluto. In terms of distance, Hydra is the fifth and most distant satellite of Pluto with a semi-major axis of its orbit of 64738 km. Its mass is (3.01±0.30)×1016 kg, with an average density of 1.220±0.150 g/cm3. The synodic period of rotation around the axis is 10.31h. The average temperature of its surface is close to 23 K. In general, the surface of Hydra turned out to be very bright with a high degree of reflection, although with significant variations in brightness. On average, it reflects almost 83% of the sunlight falling on it. This means that Hydra's surface should be covered with water ice. Like other small satellites of Pluto, Hydra's surface has a neutral spectrum. And the water ice on the surface of Hydra is quite clean and therefore does not show significant darkening. One explanation for this state is that Hydra's surface is frequently updated by micrometeorite impacts, which eject lighter material from beneath the surface of the satellite. According to crater counting data from observations by the "New Horizons" space probe, the age of Hydra's surface is estimated at about four billion years. Studies of Hydra show that it rotates chaotically. Its rotation period and axial tilt vary to the point that its axis of rotation regularly flips. The chaotic nature of Hydra's motion is largely due to the different gravitational influences of Pluto and Charon. The chaotic nature of the satellite's motion is also enhanced by its rather irregular shape. During the "New Horizons" flyby of Pluto and its moons, Hydra had a rotation period of about 10 hours; its axis of rotation was tilted nearly 110 degrees to the plane of its orbit. Like all Pluto's moons, Hydra's orbit is nearly circular and coplanar with Charon's orbit. Hydra is in a 2:3 orbital resonance with Nix, a 6:11 resonance with Styx, and a 1:6 resonance with Charon. These resonances are maintained by periodic local fluctuations in the Pluto-Charon gravitational field strength of about 5%.